Study of Servant Leadership in Building Educational Organizational Commitment at SDIT ABFA - Mohammad Subhan; Ahmad; Junaidi Efendi; Evi Febriani (TADRIS: Jurnal Pendidikan Islam, 2022)
Leadership style as an integral part of the leadership process has a close relationship with the commitment built within the organization. This commitment will arise when a leader is able to provide good service (servant) for his subordinates. This research method is qualitative with case study type. Data and data sources were obtained from informants at the SDIT ABFA Pamekasan institution through interview, observation, and documentation techniques. The results of this study indicate that the servant leadership style shown by the principal has a fairly good impact on the commitment of teachers and education personnel at SDIT ABFA Pamekasan. The servant leadership style is carried out by providing academic, supervision and administrative services in the school environment. Meanwhile, efforts and strategies to increase work commitment are carried out by establishing persuasive communication, creating a harmonious atmosphere in the school environment, and providing rewards for the achievements of subordinates